2022
DOI: 10.1021/acs.jcim.1c01510
|View full text |Cite
|
Sign up to set email alerts
|

Pose Classification Using Three-Dimensional Atomic Structure-Based Neural Networks Applied to Ion Channel–Ligand Docking

Abstract: The identification of promising lead compounds showing pharmacological activities toward a biological target is essential in early stage drug discovery. With the recent increase in available small-molecule databases, virtual high-throughput screening using physics-based molecular docking has emerged as an essential tool in assisting fast and cost-efficient lead discovery and optimization. However, the best scored docking poses are often suboptimal, resulting in incorrect screening and chemical property calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Therefore, the training time is a significant factor to consider. In our previous study [33], we demonstrated that PCN is approximately 30 times faster than a comparable 3D-CNN. We measured the times for both training and testing per pose.…”
Section: Speed Test On Pecan2mentioning
confidence: 87%
See 3 more Smart Citations
“…Therefore, the training time is a significant factor to consider. In our previous study [33], we demonstrated that PCN is approximately 30 times faster than a comparable 3D-CNN. We measured the times for both training and testing per pose.…”
Section: Speed Test On Pecan2mentioning
confidence: 87%
“…For training, we employed the widely used BCE (Binary Cross-Entropy) loss function and utilized the Adam optimizer with a learning rate of 0.001. The training was carried out with a minibatch size of 50 and ran for a total of 50 epochs, a choice guided by considerations from our previous research [33].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Computationally generated decoy poses and training data sets should be generated carefully to prevent the model from having noncausal bias, an issue where the model learns specific data patterns instead of meaningful ligand–protein interactions. , Training data sets tend to have many positive labels that lack diversity and have few or biased negative labels. ,,, Non- and poor-binders are under-reported, and computationally selected nonbinders should be verified experimentally. , There is a lack of quality and standardized data for some targets. Methods such as data set debiasing and introducing specific models to classify and rank actives from inactives , are promising regularization techniques to tackle this problem. Furthermore, it is necessary to test models in fair benchmarking data sets akin to real-world conditions. , …”
Section: Concluding Remarks and Perspectivementioning
confidence: 99%